Factors Associated With Health-Related Quality of Life among Hypertensive Patients in Kathmandu, Nepal - Ghimire, Saruna; Pradhananga, Praful; Baral, Binaya Kumar; Shrestha, Naveen (Frontiers in Cardiovascular Medicine, 2017)
Background: Nepal has a high prevalence of hypertension. While improving the overall health-related quality of life (HRQOL) is a central tenet to public health plans in developed nations, this focus has yet to be articulated in Nepal. Therefore, this study aims to identify the factors associated with HRQOL among hypertensive patients in Nepal. Method: The EQ-5D HRQOL survey was administered to 180 hypertensive patients, attending the outpatient clinic at Sahid Gangalal National Heart Center in Kathmandu, Nepal. Multiple linear regression models, adjusted for age and sex, were used to identify factors associated with HRQOL. Results: The mean age and EQVAS of the participants were 53.2 years and 63.7 respectively. Age (β= -0.56; 95%CI: -0.75 to -0.37), income (β= 0.02; 95% CI: 0.01 to 0.03), family size (β= -0.98; 95%CI: -1.89, -0.07), number of antihypertensive drugs use (β= 4.62; 95%CI: 1.33, 7.90), and compliance to dietary salt advise (β=4.86; 95% CI: 0.29 to 9.43) were significant factors associated with HRQOL among participants. Additionally, levels of education and self-perceived health were associated in a positive gradient to HRQOL. In mediation analysis, both, dietary low salt compliance and use of antihypertensive drugs, had a significant direct effect on HRQOL and the use of antihypertensive drugs did not significantly mediate the relationship between dietary salt compliance and HRQOL. Conclusion: Various factors were found to be associated with HRQOL among hypertensive patients in Kathmandu. Assessing HRQOL is a valuable technique to identify populations in need of services and interventions. This assessment can serve as a baseline, and in conjunction with multiple stakeholders, can guide public health policy, planning, and practices, especially those aimed towards improving the HRQOL of Nepalese with hypertension.